Physicochemical Properties of Iranian Varieties/Lines of Safflower Oil and Seed as a Rich Source of ω-6 - E Morovati; MA Sahari; M Barzegar (Institue of Medicinal Plants, ACECR, 2010)
Background: High in take of saturated fatty acids and animal fats, increases cardiovascular disease, cancer and obesity whereas ω-3 and ω-6 poly unsaturated fatty acids as necessary fatty acids have preventive effect on aforementioned disease. Necessity of ω-3 and ω-6 acids and limitation of their sources with increasing of population, make scientists to find other sources. Objective: For optimal usage of internal oil resources such as safflower, increasing of its cultivation and existence of Saffola as a mutative variety (high amount of oleic acid), this research for investigation the physicochemical characteristics of seed and oil of six variety/line of safflower farmed in Iran and the comparison of type and amount of oil and classification of them to oleic or linoleic acid group was done. Methods: Varieties/lines of Iranian safflower including Goldasht (as a spring variety), Mahali Esfehan, Esfehan 14, Esfehan 28 (as spring lines), Padide (as a fall variety) and Sina (as a day land farming variety) were provided )Provision Institute and Improvement of Plant and Seed located in Karaj), and characteristics of safflower seeds (oil, protein, ash, moisture and fiber contents) and its extracted oil (acid, iodine and saponification values, fatty acids profile and color) were investigated. Results: Results indicated that the studied varieties/lines were only linoleic safflower (no any oleic safflower). Conclusion: Iranian safflower varieties/lines have the highest amount ofω -6 (72.6 - 75078) in comparison with other oil sources which are valuable and necessary fatty acids.